Effects of ascorbic acid on in vitro culture of bovine preantral follicles - Andrade, Evelyn R.; Van Den Hurk, Robert; Lisboa, Lívia A.; Hertel, Mariana F.; Melo-Sterza, Fabiana A.; Moreno, Kleber; Bracarense, Ana Paula F.R.L.; Landim-Alvarenga, Fernanda C. [UNESP]; Seneda, Marcelo M.; Alfieri, Amauri A. (Cambridge University Press (CUP), 2012)
The objective of this study was to evaluate the effects of adding ascorbic acid to the media for in vitro culture of cattle ovarian fragments and to determine their effects on growth activation and viability of early-stage follicles. The ovarian cortex was divided into small fragments; one fragment was immediately fixed (control) and the other fragments were cultured in minimum essential medium (MEM) supplemented or not with various doses of ascorbic acid. Ovarian tissue was processed for histology, transmission electron microscopy (TEM) and immunohistochemical demonstration of proliferating cell nuclear antigen (PCNA). Compared with control fragments, the percentage of primordial follicles was reduced (p < 0.05) and the percentage of growing follicles had increased (p < 0.05) in cultured cortical fragments, independent of the tested medium or incubation time. Furthermore, compared with control tissue, culture of ovarian cortex for 8 days reduced the percentages of healthy, viable follicles (p < 0.05), but not when cultures were supplemented with 25, 50 or 100 μg/ml of ascorbic acid. Ultrastructural and immunohistochemical analysis of 8 day cultured ovarian cortical fragments, however, showed the integrity and viability of follicles only when fragments were cultured in presence of 50 μg/ml of ascorbic acid. In conclusion, this study demonstrated that addition of ascorbic acid to MEM at a concentration of 50 μg/ml not only stimulates the activation of 8 day in vitro cultured cattle primordial follicles and subsequent growth of activated follicles, but also safeguards the viability of these early-stage follicles. © 2012 Copyright Cambridge University Press.
Keywords: Ascorbic acid; Cattle; In vitro culture; Preantral follicles; ascorbic acid; cycline; follitropin; animal; cattle; culture medium; drug effect; female; metabolism; ovary follicle; transmission electron microscopy; ultrastructure; Animals; Ascorbic Acid; Culture Media; Female; Follicle Stimulating Hormone; Microscopy, Electron, Transmission; Ovarian Follicle; Proliferating Cell Nuclear Antigen; Bos; Bovinae